2021
DOI: 10.1002/smll.202101678
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale FasL Organization on DNA Origami to Decipher Apoptosis Signal Activation in Cells

Abstract: Cell signaling is initiated by characteristic protein patterns in the plasma membrane, but tools to decipher their molecular organization and activation are hitherto lacking. Among the well‐known signaling pattern is the death inducing signaling complex with a predicted hexagonal receptor architecture. To probe this architecture, DNA origami‐based nanoagents with nanometer precise arrangements of the death receptor ligand FasL are introduced and presented to cells. Mimicking different receptor geometries, thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 61 publications
2
43
0
Order By: Relevance
“…Work studying Fas/FasL, which induces apoptosis similarly to TRAIL/DR5, demonstrated the ligand spacing of FasL affected the apoptosis rate, which could explain increased caspase activity in the phase segregated 2:1 and 3:1 DSPC:DOPC TRAIL compositions but not DOPC TRAIL. 27 These results confirmed the mode of TRAIL-vesicle mediated cytotoxicity was through caspase-mediated apoptosis, and that concentrating TRAIL into vesicle membrane domains increased caspase activity.…”
Section: Trail Conjugation To Phase Segregated Lipids Enhances Trail-mediated Apoptosissupporting
confidence: 60%
See 1 more Smart Citation
“…Work studying Fas/FasL, which induces apoptosis similarly to TRAIL/DR5, demonstrated the ligand spacing of FasL affected the apoptosis rate, which could explain increased caspase activity in the phase segregated 2:1 and 3:1 DSPC:DOPC TRAIL compositions but not DOPC TRAIL. 27 These results confirmed the mode of TRAIL-vesicle mediated cytotoxicity was through caspase-mediated apoptosis, and that concentrating TRAIL into vesicle membrane domains increased caspase activity.…”
Section: Trail Conjugation To Phase Segregated Lipids Enhances Trail-mediated Apoptosissupporting
confidence: 60%
“…38 A similar study found precise ligand spatial orientation was critical for Fas (CD95) signaling, another TNF superfamily receptor with a similar signaling pathway as DR5. 27 We hypothesize that controlling TRAIL spatial orientation on lipid vesicles by using lipid domains most likely increases DR5-mediated apoptosis by approaching this critical inter-ligand distance.…”
Section: Dr5/dr4 Expression Affects the Impact Of Phase Segregated Trail Vesiclesmentioning
confidence: 98%
“…Using a DNA origami platform, the FasL ligands were immobilized and arranged in different geometries to test the effect of clustering on apoptosis efficiency in HeLa cells overexpressing the Fas receptor. Hexagonally arranged ligands signaled orders of magnitude better than soluble ligands [ 25 ]. Furthermore, ligands arranged in a hexagon with the right geometry doubled the rate of apoptosis compared to ligands arranged in pairs [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Instead, commercially available tetravalent streptavidin (tSAv) has often been used, and while it offers in principle three sites for ligand binding, only one may be accessible due to steric hindrance when surface-attached 33 . Differences in the cellular response to a ligand presented via mSAv and tSAv have been observed yet attributed to the presence of a flexible linker in the mSAv construct 7 . To assess biochemical and functional consequences of tSAv valency in more detail, we designed the construct H57-tSAv in analogy to H57-dSAv, but replaced the divalent with tetravalent streptavidin (SI Fig.…”
Section: For Each Dose-response Curve Data Are From At Least Two Independent Experiments Involving T-cells Isolated From Two Different MImentioning
confidence: 99%
“…By using short oligonucleotides ("staples") to guide the folding of a long single stranded DNA scaffold, it is not only possible to program the shape of a DNA origami structure but also to arrange functional elements with nanometer resolution and precision 1 . Proteindecorated DNA origami structures have thus far been interfaced with cells as soluble agents 2,3 , attached to a solid substrate 4,5 or anchored to a fluid supported lipid bilayer (SLB) 6,7 ; biological questions addressed range from studying cellular signaling and adhesion processes [2][3][4][5][6]8,9 , to creating synthetic multienzyme cascades 10,11 to more and more elaborate robotic DNA machines 12 .…”
mentioning
confidence: 99%